Echocardiographic evidence of left ventricular hypertrophy in a general aged population - Lindroos, Magnus; Kupari, Markku; Heikkilä, Juhani; Tilvis, Reijo (The American journal of cardiology, 1994)
The purpose of this study was to measure the frequency of left ventricular (LV) hypertrophy in old age. Random subjects born in 1904, 1909, and 1914 (n = 501), and 76 born in 1920 to 1935 were studied. All subjects underwent clinical and echocardiographic investigation. An electrocardiogram was obtained in 449 subjects. Complete data for calculation of LV mass corrected for body size were available in 422 of the studied subjects (73%). LV hypertrophy was defined as calculated LV mass exceeding either an internal standard of the Helsinki Aging Study, earlier published limits from the Framingham Heart Study, or criteria from Devereux et al. LV wall thickness and mass were positively related to age. Hypertrophy was present in both sexes, the rate even exceeding 70% in the oldest cohort aged 85 to 86 years using the Framingham and Devereux limits. LV hypertrophy (LV mass exceeding defined limits after correction for body height) was significantly and independently related to age, systolic blood pressure, body mass index, and mitral regurgitation. A sustained apex beat, third heart sound, and electrocardiographic changes were significantly more frequent in the group with echocardiographic hypertrophy, although with considerable overlapping. The fourth heart sound was unrelated to hypertrophy. Use of age-independent criteria result in an extremely high prevalence of LV hypertrophy in old age. This is partly due to age-related diseases increasing LV mass, but also partly to an independent effect of age. The usefulness of clinical signs for detecting LV hypertrophy is limited in old age.